Drug Use and Youth Cultural Practice in Russia, 2002 - Omel'chenko, E., Ulyanovsk State University (Russia); Pilkington, H., University of Birmingham, Centre for Russian and East European Studies (2006)
Abstract copyright UK Data Service and data collection copyright owner. This study investigated the degree to which substance use (illicit drugs and alcohol) has become 'normalised' among young Russians. The study used three data gathering methods: a quantitative survey based on a self-completion questionnaire was distributed to three cohorts of young people - 14/15-year-olds ('8th class' in school), 16/17-year-olds ('10th class') and 18/19-year-olds (1st years in higher/further education institutions). The survey was fielded in a total of nine small, medium and large cities in three regions of Russia parallel semi-structured interviews were conducted with a sub-sample of survey respondents (95 across all 9 sites a 6-week period of ethnographic follow-up research was conducted 12 months later, with a total of 19 groups of young people, in 3 of the 9 sites in which the survey and interview elements of the research were conducted The study was conducted in the Komi Republic, Samara and Krasnodar Territory regions of Russia. This ensured a geographical span from the Black Sea to the Arctic Circle, and therefore encompassed the cannabis-growing regions of the south, the drugs trafficking routes in the middle Volga region, and the isolated far north of the country. The study investigated 'normalisation' of drug and alcohol use in terms of individual use, by gathering prevalence data and qualitative research charting drugs decisions and drugs careers. It also considered the role of young people's immediate environment (especially the friendship group) and the wider environment (especially the discursive construction of drug use, and the presence of drugs in the youth cultural environment). The range of drugs education and prevention work being conducted in the three regions was also investigated, through a series of expert interviews and by noting the young people's experience of the effectiveness of these interventions. This mixed methods data collection includes transcripts of the semi-structured interviews ...